Research methodology for determining the economic efficiency of using low-intensity irrigation systems in mountain farming in Azerbaijan - Z. H, Prof. RANS ALIYEV (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2018)
For a well-known purpose in 2010-2015, Guba-Khachmaz RAEM, Tartar and RAEM Shamakhi TSB have been confirmed by numerous research findings in the field of mountain watering, in terms of the development of irrigation, the mountainous slopes include soybean, sugar beet, trees, and germination (barley, wheat, etc.), the microcirculation method was not cost-effective in terms of efficiency, and preventive measures such as surface soil wash, sliding, irrigation and drowning, erosion characteristic for mountainous terrain zones , which is of particular importance, confirms the feasibility study of the farm calculated with the following formula.